Respuestas

2013-12-27T20:45:01+01:00

51) rs+4st=R/  s(r+4t)   53) 3a 2b 2-6a 2b= R/ 3a 2b (b-2)     55) 9x2y2+15xy4= 3xy2 (3x+5y2)    57) 4x2+5x-6= (4x-3) (x+2)   59) 4x2-4x-15= (2x-5) (2x+3)   61) 16y2-14y-15= (8y+5) (2y-3)   63) 9z2-12z+4= (3z-2) (3z-2)   65) 12x2+50c+48 = 2(3c+8) (2c+3)   67) 4r2-25t2= (2r-2t) (2r+5t)   69) 50x2+45xy-18y2= (5x+6) (10x-3)   71) 64w4-36s2= 4(4w2-35) (4w2+35)   73) 36z2+60z+25 =  (6z+5) (6z+5)  R/ (6z+5)2   75) 27x3-y3=        3x-y = (3x-y) ((3x)2+(3x)(y) +(y)2         R/ (3x-y)  (9x2+3xy+y2 )      77) 27a3 +64b3= (3a+4b) ((3a)2-(3ª)(4b) +(4b)2                        = (3a+4b) (9a 2-12ab+16b2)                                                                                                     79) 8x6-125 = (2x2-5) ((2x2)2+(2x2)(5) +(5)2 = (2x2-5) (4x4+10x2+25)   81) 6ax-3ay+2bx-by= (6ax-´3ay) (2bx-by) 3a (2x-y) b (2x-y) R/ (3a+b) (2x-y)       83) 40zw+8x2w-35z-7x2 (40zw-35z) (8x2w-7x2) 5z (8w-7) x2(8w-7)   85) a3-a2b+ab2.b3=  (a3- a2b) (ab2-b3) a2(a-b) b2(a-b) R/ (a2+b2) (a-b)